2019
DOI: 10.3389/fnhum.2019.00027
|View full text |Cite
|
Sign up to set email alerts
|

Neural Connectivity in Syntactic Movement Processing

Abstract: Linguistic theory suggests non-canonical sentences subvert the dominant agent-verb-theme order in English via displacement of sentence constituents to argument (NP-movement) or non-argument positions (wh-movement). Both processes have been associated with the left inferior frontal gyrus and posterior superior temporal gyrus, but differences in neural activity and connectivity between movement types have not been investigated. In the current study, functional magnetic resonance imaging da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
2
5
0
1
Order By: Relevance
“…Our f MRI results showed that compared to the control task, the processing of deep unaccusative sentences, unergative sentences, and passive sentences in Mandarin Chinese elicited greater activation in the LIFG, the LSTG, and the LMTG. The results indicate that these regions might perform a significant function in processing language, which has consistently been supported by numerous studies exploring the neural mechanisms of language processing (e.g., [30,[39][40][41][42]). In addition, the processing of the control condition elicited greater activation in the occipital lobe, which was related to visual processing [43].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our f MRI results showed that compared to the control task, the processing of deep unaccusative sentences, unergative sentences, and passive sentences in Mandarin Chinese elicited greater activation in the LIFG, the LSTG, and the LMTG. The results indicate that these regions might perform a significant function in processing language, which has consistently been supported by numerous studies exploring the neural mechanisms of language processing (e.g., [30,[39][40][41][42]). In addition, the processing of the control condition elicited greater activation in the occipital lobe, which was related to visual processing [43].…”
Section: Discussionsupporting
confidence: 72%
“…Consequently, in Mandarin Chinese, the subject of passive verbs should experience an additional syntactic movement from the object position to the subject position in the generation process. Theoretical accounts [24,28,48] and experimental studies [30,32] also agree that Mandarin Chinese passive sentences are structures derived by a syntactic movement, which is consistent with that of many other languages. According to previous theoretical and experimental research, the LSTG concerning passive sentence processing in the present experiment was likely related to the syntactic movement of the subject in passive sentences.…”
Section: The Lstgsupporting
confidence: 62%
See 2 more Smart Citations
“…。还有 (Hackett, 2011;Yi et al, 2019;Hickok & Poeppel, 2007;Friederici, 2012;Gierhan, 2013;Skeide & Friederici, 2016 Enatsu et al, 2013;Matsumoto et al, 2017 (den Ouden et al, 2012 ;Europa et al, 2019;Friederici, 2012;Gierhan, 2013;Hickok & Poeppel, 2007;Schneider et al, 2016) (Europa et al, 2019;Friederici, 2012;Liu et al, 2020;Lyu et al, 2016;Zhang et al, 2019 )。此外, 大脑也会利用自上而下的反馈途径来协助快速识 别信息 (Friederici, 2012;Lyu et al, 2016;Oestreich et al, 2018;Zhang et al, 2019 ) (Enatsu et al, 2013;Entz et al, 2014;Garell, 2013;Kanno et al, 2018;Keller et al, 2011;Matsumoto et al, 2004;Nakae et al, 2020;Nishida et al, 2017) Keller et al, 2011;Entz et al, 2014;Nishida et al, 2017) 4), 440-445. Amunts, K., Lenzen, M., Friederici, A. D., Schleicher, A.,…”
unclassified